Real-life characteristics and management of patients with fibrosing interstitial lung disease: INSIGHTS-ILD registry - Behr, Jürgen; Kreuter, Michael; Guenther, Andreas U.; Bonella, Francesco; Pittrow, David; Pausch, Christine; Seeliger, Benjamin; Prasse, Antje; Skowasch, Dirk; Wilkens, Henrike; Kabitz, Hans-Joachim; Wirtz, Hubert; et al. (ERJ Open Research, 2025)
Background: This study aims to report real-life data on the characteristics and treatment patterns of patients with fibrosing interstitial lung disease (ILD; except idiopathic pulmonary fibrosis) across multiple specialised centres in Germany. Eligibility criteria included ILD affecting >10% of lung parenchyma on high-resolution computed tomography, a single breath diffusion capacity for carbon monoxide (D LCO) ≤80% predicted and active treatment of lung disease. Methods: As of the interim analysis cut-off, 655 patients (mean±sd age 65.9±11.7 years, 54.5% male) were included. The most common ILD subtypes were fibrosing hypersensitivity pneumonitis (31.2%), fibrosing ILD (22.0%), rheumatoid arthritis and connective tissue disease ILDs (13.0%) and unclassifiable fibrosing ILD (13.0%). Results: Lung function metrics included total lung capacity at 68.3±17.6% predicted, forced vital capacity at 69.8±19.8% predicted, forced expiratory volume in 1 s at 73.7±19.5% predicted and D LCO at 33.8±15.6% predicted. Current treatments included oral steroids (62.6%), antifibrotic therapy (50.7%), azathioprine (14.4%), methotrexate (10.2%) and mycophenolate mofetil (11.1%). Patients on antifibrotic therapy were typically older at diagnosis and registry inclusion, more often male, had more comorbidities, a lower 6-min walk distance and reduced lung function metrics compared with those not on antifibrotic therapy. Notably, 27.3% of the patients on antifibrotic therapy did not meet progression criteria (INBUILD), whereas 40.1% of patients not receiving antifibrotic therapy did meet those criteria. Conclusion: The patient characteristics observed align with those observed in randomised controlled trials and other noninterventional studies. Patients on antifibrotic therapy generally had more severe disease profiles.
Gesehen am 29.10.2025